2011
DOI: 10.1186/1472-6947-11-47
|View full text |Cite
|
Sign up to set email alerts
|

Integrating an internet-mediated walking program into family medicine clinical practice: a pilot feasibility study

Abstract: BackgroundRegular participation in physical activity can prevent many chronic health conditions. Computerized self-management programs are effective clinical tools to support patient participation in physical activity. This pilot study sought to develop and evaluate an online interface for primary care providers to refer patients to an Internet-mediated walking program called Stepping Up to Health (SUH) and to monitor participant progress in the program.MethodsIn Phase I of the study, we recruited six pairs of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 50 publications
1
18
0
Order By: Relevance
“…Although clinicians noted that the graphical display of patients' walking progress was informative, they found it inconvenient that data were not integrated into their EHR. 16 The extra time required to locate the Web site, remember passwords, and log-in as well as lack of time for physical activity discussions during patient visits presented barriers to using the interface. Langstrup 20 had patients with asthma record daily peak flow readings in an online diary that could be accessed by healthcare personnel.…”
Section: Acceptability Of Rmt In Primary Care: a Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…Although clinicians noted that the graphical display of patients' walking progress was informative, they found it inconvenient that data were not integrated into their EHR. 16 The extra time required to locate the Web site, remember passwords, and log-in as well as lack of time for physical activity discussions during patient visits presented barriers to using the interface. Langstrup 20 had patients with asthma record daily peak flow readings in an online diary that could be accessed by healthcare personnel.…”
Section: Acceptability Of Rmt In Primary Care: a Reviewmentioning
confidence: 99%
“…11,16,17,[19][20][21][22][23][25][26][27] Three studies were conducted in the United States, 11,16,19 one in Canada, 21 one in Denmark, 20 two in Germany, 22,23 and one in Korea, 25 and two studies in the United Kingdom were published in three reports. 17,26,27 Clinicians in several studies conveyed positive views about RMT, and some reported RMT resulted in a decrease in workload due to delegation of activities to ancillary staff.…”
Section: Key Question 1 Views Of Primary Care Clinicians On Incorpormentioning
confidence: 99%
See 3 more Smart Citations